A perovskite solar cell based on 1,4-diiodotetrafluorobenzene doped hole transport layer and preparation method thereof

By doping 1,4-diiodotetrafluorobenzene into the spiro-OMeTAD hole transport layer in perovskite solar cells, and using halogen bonds to form chemical constraints with TBP, the perovskite corrosion and spiro-OMeTAD dedoping problems caused by TBP are solved, and more stable carrier transmission and higher battery performance are achieved.

CN114583065BActive Publication Date: 2025-03-04JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210206972.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-03-04
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

When existing perovskite solar cells use TBP dopants, they will cause corrosive decomposition of perovskites and damage the charge transport capability of the spiro-OMeTAD hole transport layer, reducing the performance of the battery.

Method used

By doping 1,4-diiodotetrafluorobenzene into the spiro-OMeTAD hole transport layer, chemical binding is formed with TBP using halogen bonds, which inhibits the corrosion of TBP on perovskites and the dedoping effect of spiro-OMeTAD.

Benefits of technology

The defect density of the perovskite layer is reduced, the charge carrier transmission is stabilized, and the performance and stability of perovskite and spiro-OMeTAD films are improved, thereby improving the performance of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114583065B_ABST
    Figure CN114583065B_ABST
Patent Text Reader

Abstract

A perovskite solar cell based on a 1,4-diiodotetrafluorobenzene doped hole transport layer and a preparation method thereof, belonging to the technical field of perovskite solar cells. 2 The present invention comprises an electron transport layer, a perovskite active layer, a phenethylammonium iodide surface passivation layer, a spiro-OMeTAD hole transport layer and an Ag electrode. The present invention dopes 1,4-diiodotetrafluorobenzene into the spiro-OMeTAD hole transport layer, and utilizes the halogen bond formed between 1,4-diiodotetrafluorobenzene and the dopant TBP in spiro-OMeTAD to inhibit the corrosion of TBP on the perovskite, thereby reducing the defect density of the perovskite film. At the same time, the dedoping effect of spiro-OMeTAD induced by TBP is inhibited, the conductivity of the spiro-OMeTAD film is stabilized, and the charge can be well transmitted, thereby improving the performance of the perovskite battery device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and specifically relates to a perovskite solar cell based on a 1,4-diiodotetrafluorobenzene-doped hole transport layer and a preparation method thereof. Background Art

[0002] Perovskite solar cells have the advantages of low manufacturing cost, high conversion efficiency, and the ability to prepare flexible devices, and have attracted widespread attention from researchers. Among them, positive perovskite solar cells with tin dioxide (SnO2) as the electron transport layer and 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD) as the hole transport layer have been widely studied for their high efficiency. The intrinsic conductivity and carrier mobility of pure spiro-OMeTAD are very low, so dopants are needed to improve its electrical properties. Currently, the commonly used dopants are lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 4-tert-butylpyridine (TBP). Although the addition of TBP can promote the dissociation of LiTFSI, control the morphology of the film, and increase the equivalent carrier mobility, TBP will generate a complex with lead iodide on the one hand to induce the corrosive decomposition of perovskite and increase the defect density of the perovskite film, and on the other hand, it will reduce the oxidized spiro-OMeTAD molecules and damage the charge transfer capacity of the spiro-OMeTAD hole transport layer, thereby reducing the performance of the perovskite solar cell. In the present invention, the halogen bond formed between 1,4-diiodotetrafluorobenzene and TBP is used to chemically bind TBP, and it is doped into the spiro-OMeTAD hole transport layer, thereby inhibiting the corrosion of TBP on perovskite and the dedoping effect on spiro-OMeTAD, reducing the defect density of the perovskite layer, achieving stable and good carrier transport, and thus improving the performance of the perovskite solar cell. Summary of the invention

[0003] The present invention aims to provide a perovskite solar cell based on a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer and a preparation method thereof.

[0004] The perovskite solar cell based on a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer described in the present invention is characterized in that it is composed, from bottom to top, of an indium tin oxide (ITO) conductive glass substrate, a SnO2 electron transport layer, a perovskite active layer, a phenethylammonium iodide surface passivation layer, a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer and an Ag electrode.

[0005] The present invention dopes 1,4-diiodotetrafluorobenzene into a spiro-OMeTAD hole transport layer. 1,4-diiodotetrafluorobenzene and a dopant TBP of spiro-OMeTAD are bonded via a halogen bond. The strong chemical interaction is utilized to bind TBP, thereby inhibiting the reaction between TBP and lead iodide and oxidized spiro-OMeTAD, thereby inhibiting the corrosive decomposition of perovskite and the dedoping of spiro-OMeTAD, reducing the defect density of the perovskite layer, stabilizing the charge carrier transport, improving the performance and stability of the perovskite and spiro-OMeTAD films, and ultimately improving the performance of the perovskite solar cell. Among them, the thickness of the SnO2 electron transport layer is 20 to 30 nm, the thickness of the perovskite active layer is 0.8 to 1.2 μm, the thickness of the phenethylammonium iodide surface passivation layer is 6 to 12 nm, the thickness of the 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer is 200 to 300 nm, and the thickness of the Ag electrode is 80 to 100 nm.

[0006] The method for preparing a perovskite solar cell based on a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer according to the present invention comprises the following steps:

[0007] 1) Cleaning of substrate

[0008] The ITO conductive glass substrate was ultrasonically cleaned with acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then dried with nitrogen gas;

[0009] 2) Preparation of SnO2 electron transport layer

[0010] The SnO2 aqueous dispersion is diluted with deionized water at a volume ratio of 1:3-5, and the concentration of SnO2 after dilution is 2.5-3.75wt%, and then statically spin-coated on the ITO conductive glass substrate obtained in step 1) at a rotation speed of 3000-4500rpm for 20-30s, and then annealed at 150-180°C for 20-30min, so as to obtain a SnO2 electron transport layer with a thickness of 20-30nm on the ITO conductive glass substrate; static spin coating means that after the solution is dripped onto the substrate, the substrate starts to rotate again under the drive of the turntable;

[0011] 3) Preparation of perovskite active layer

[0012] (a) Preparation of active layer solution

[0013] Dissolve 645.4-737.6 mg of lead iodide in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of N,N-dimethylformamide (DMF) to dimethyl sulfoxide (DMSO) is 8-10:1, and stir at a stirring speed of 500-700 rpm for 15-20 hours to obtain a lead iodide solution; dissolve 85-95 mg of formamidine hydroiodide, 6-7 mg of methylammonium iodide and 8-10 mg of methylammonium chloride in 1 mL of isopropanol, and stir at a stirring speed of 500-700 rpm for 15-20 hours to obtain an organic mixture solution;

[0014] (b) Preparation of perovskite active layer

[0015] 20 to 30 μL of lead iodide solution is statically spin-coated onto the SnO2 electron transport layer at a rotation speed of 1800 to 2200 rpm for 20 to 30 seconds, and then annealed at 65 to 75°C for 50 to 70 seconds to obtain a lead iodide film; subsequently, 60 to 120 μL of an organic mixture solution is dynamically spin-coated onto the lead iodide film at a rotation speed of 1800 to 2200 rpm for 25 to 35 seconds, the organic mixture reacts with the lead iodide, and then annealed at 140 to 160°C for 15 to 30 minutes to obtain a perovskite active layer with a thickness of 0.8 to 1.2 μm; dynamic spin coating refers to dripping the solution onto the substrate after the substrate starts to rotate driven by a turntable;

[0016] 4) Preparation of surface passivation layer of phenethylammonium iodide

[0017] Dissolve 2-4 mg of phenethylammonium iodide in 1 mL of isopropanol, and stir at a stirring speed of 500-700 rpm for 15-20 hours to obtain a phenethylammonium iodide solution; dynamically spin-coat the phenethylammonium iodide solution onto the perovskite active layer at a rotation speed of 3000-5000 rpm for 30-40 seconds to prepare a phenethylammonium iodide surface passivation layer with a thickness of 6-12 nm;

[0018] 5) Preparation of 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer

[0019] (a) Preparation of hole transport layer solution

[0020] 70-80 mg spiro-OMeTAD was dissolved in 1 mL chlorobenzene, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a spiro-OMeTAD original solution; 500-540 mg LiTFSI was dissolved in 1 mL acetonitrile, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a LiTFSI acetonitrile solution; 9.2-27.7 mg 1,4-diiodotetrafluorobenzene was dissolved in 1 mL TBP, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a 1,4-diiodotetrafluorobenzene TBP solution; 17-18 μL LiTFSI acetonitrile solution and 28-29 μL were added to 1 mL spiro-OMeTAD original solution. The TBP solution of 1,4-diiodotetrafluorobenzene is stirred at a stirring speed of 500 to 700 rpm for 10 to 15 hours to obtain a hole transport layer solution doped with 1,4-diiodotetrafluorobenzene;

[0021] (b) Preparation of hole transport layer

[0022] The hole transport layer solution is statically spin-coated on the surface passivation layer of phenylethylammonium iodide at a rotation speed of 3500-4500 rpm for 20-30 seconds to prepare a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer with a thickness of 200-300 nm;

[0023] 6) Preparation of Ag electrode

[0024] At a pressure of 1×10 -4 ~1×10 -3 Pa, Ag was evaporated on the 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer with a thickness of 80-100 nm and a growth rate of Thus, the perovskite solar cell based on the 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer of the present invention is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : A schematic diagram of the structure of a perovskite solar cell based on a spiro-OMeTAD hole transport layer doped with 1,4-diiodotetrafluorobenzene according to the present invention;

[0026] Figure 2 : Current density-voltage characteristic curves of the perovskite solar cell based on 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer prepared by the present invention and the conventional perovskite solar cell based on undoped spiro-OMeTAD hole transport layer under illumination;

[0027] like Figure 1As shown, 1 is an ITO conductive glass substrate, 2 is a SnO2 electron transport layer, 3 is a perovskite active layer and a phenethylammonium iodide surface passivation layer (the thickness of the phenethylammonium iodide surface passivation layer is only 6 to 12 nm), 4 is a 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer, and 5 is an Ag electrode.

[0028] like Figure 2 As shown, at 100mw / cm 2 The current density-voltage characteristic curve of the battery was measured under the illumination of a solar simulator, wherein curve A is a traditional device and curve B is the device described in the present invention. Figure 2 It is shown that compared with traditional perovskite solar cells, the cell device prepared by the present invention has significantly improved open circuit voltage, fill factor and conversion efficiency. DETAILED DESCRIPTION

[0029] Example 1

[0030] 1) Cleaning of substrate

[0031] The ITO conductive glass substrate was ultrasonically cleaned with acetone, ethanol and deionized water for 15 min respectively, and then dried with nitrogen gas;

[0032] 2) Preparation of SnO2 electron transport layer

[0033] The commercial SnO2 aqueous dispersion was diluted with deionized water at a volume ratio of 1:4 to obtain a SnO2 aqueous dispersion, and the concentration of SnO2 after dilution was 3wt%; it was then statically spin-coated on the ITO conductive glass substrate obtained in step 1) at a rotation speed of 4000rpm for 30s, and then annealed at 150°C for 20min, thereby obtaining a SnO2 electron transport layer with a thickness of 25nm on the ITO conductive glass substrate.

[0034] 3) Preparation of perovskite active layer

[0035] (a) Preparation of active layer solution

[0036] 691.5 mg of lead iodide was dissolved in 1 mL of a mixed solvent of DMF and DMSO in a volume ratio of 9:1, and the mixture was stirred at a stirring speed of 600 rpm for 18 hours to obtain a lead iodide solution; 90 mg of formamidine hydroiodide, 6.39 mg of methylammonium iodide and 9 mg of methylammonium chloride were dissolved in 1 mL of isopropanol, and the mixture was stirred at a stirring speed of 600 rpm for 18 hours to obtain an organic mixture solution;

[0037] (b) Preparation of active layer

[0038] The lead iodide solution was statically spin-coated onto the SnO2 electron transport layer at a speed of 2000 rpm for 30 seconds, and then annealed at 70°C for 60 seconds to obtain a lead iodide film; subsequently, 100 μL of the organic mixture solution was statically spin-coated onto the lead iodide film at a speed of 2000 rpm for 30 seconds, and then annealed at 150°C for 30 minutes to form a perovskite active layer with a thickness of 1 μm;

[0039] 4) Preparation of surface passivation layer of phenethylammonium iodide

[0040] 3 mg of phenethylammonium iodide was dissolved in 1 mL of isopropanol and stirred at 600 rpm for 18 h to obtain a phenethylammonium iodide solution; the phenethylammonium iodide solution was dynamically spin-coated on the perovskite active layer at 4000 rpm for 30 s to prepare a phenethylammonium iodide surface passivation layer with a thickness of 8 nm;

[0041] 5) Preparation of 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer

[0042] (a) Preparation of hole transport layer solution

[0043] 72.3 mg spiro-OMeTAD was dissolved in 1 mL chlorobenzene, and stirred at a stirring speed of 600 rpm for 1 h to obtain a spiro-OMeTAD original solution; 520 mg LiTFSI was dissolved in 1 mL acetonitrile, and stirred at a stirring speed of 600 rpm for 1 h to obtain a LiTFSI acetonitrile solution; 18.5 mg 1,4-diiodotetrafluorobenzene was dissolved in 1 mL TBP, and stirred at a stirring speed of 600 rpm for 1 h to obtain a 1,4-diiodotetrafluorobenzene TBP solution; 17.6 μL LiTFSI acetonitrile solution and 28.5 μL 1,4-diiodotetrafluorobenzene TBP solution were added to the spiro-OMeTAD original solution, and stirred at a stirring speed of 600 rpm for 12 h to obtain a hole transport layer solution;

[0044] (b) Preparation of hole transport layer

[0045] The hole transport layer solution was statically spin-coated on the surface passivation layer of phenethylammonium iodide at a rotation speed of 4000 rpm for 30 seconds to prepare a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer with a thickness of 200 nm;

[0046] 6) Preparation of Ag electrode

[0047] At a pressure of 8×10 -4 Pa, a Ag electrode was evaporated on the 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer with a thickness of 100 nm and a growth rate of Thus, the perovskite solar cell based on the 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer of the present invention is obtained.

Claims

1. A method for preparing a perovskite solar cell based on a spiro-OMeTAD hole transport layer doped with 1,4-diiodotetrafluorobenzene, the steps of which are as follows: 1) Cleaning of substrate The ITO conductive glass substrate was ultrasonically cleaned with acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then dried with nitrogen gas; 2) Preparation of SnO2 electron transport layer The SnO2 aqueous dispersion is diluted with deionized water at a volume ratio of 1:3-5, and the concentration of the diluted SnO2 is 2.5-3.75wt%, and then statically spin-coated on the ITO conductive glass substrate obtained in step 1) at a rotation speed of 3000-4500 rpm for 20-30 seconds, and then annealed at 150-180° C. for 20-30 minutes, thereby obtaining a SnO2 electron transport layer on the ITO conductive glass substrate; 3) Preparation of perovskite active layer (a) Preparation of active layer solution Dissolve 645.4-737.6 mg of lead iodide in 1 mL of a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 8-10:1, and stir at a stirring speed of 500-700 rpm for 15-20 hours to obtain a lead iodide solution; dissolve 85-95 mg of formamidine hydroiodide, 6-7 mg of methylammonium iodide and 8-10 mg of methylammonium chloride in 1 mL of isopropanol, and stir at a stirring speed of 500-700 rpm for 15-20 hours to obtain an organic mixture solution; (b) Preparation of perovskite active layer 20 to 30 μL of lead iodide solution is statically spin-coated onto the SnO2 electron transport layer at a rotation speed of 1800 to 2200 rpm for 20 to 30 seconds, and then annealed at 65 to 75°C for 50 to 70 seconds to obtain a lead iodide film; subsequently, 60 to 120 μL of an organic mixture solution is dynamically spin-coated onto the lead iodide film at a rotation speed of 1800 to 2200 rpm for 25 to 35 seconds, the organic mixture reacts with the lead iodide, and then annealed at 140 to 160°C for 15 to 30 minutes to obtain a perovskite active layer; 4) Preparation of surface passivation layer of phenethylammonium iodide Dissolving 2-4 mg of phenethylammonium iodide in 1 mL of isopropanol, stirring at a stirring speed of 500-700 rpm for 15-20 hours to obtain a phenethylammonium iodide solution; dynamically spin-coating the phenethylammonium iodide solution onto the perovskite active layer at a rotation speed of 3000-5000 rpm for 30-40 seconds to prepare a phenethylammonium iodide surface passivation layer; 5) Preparation of 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer (a) Preparation of hole transport layer solution 70-80 mg spiro-OMeTAD was dissolved in 1 mL chlorobenzene, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a spiro-OMeTAD original solution; 500-540 mg LiTFSI was dissolved in 1 mL acetonitrile, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a LiTFSI acetonitrile solution; 9.2-27.7 mg 1,4-diiodotetrafluorobenzene was dissolved in 1 mL TBP, and stirred at a stirring speed of 500-700 rpm for 1-2 h to obtain a 1,4-diiodotetrafluorobenzene TBP solution; 17-18 μL LiTFSI acetonitrile solution and 28-29 μL were added to 1 mL spiro-OMeTAD original solution. The TBP solution of 1,4-diiodotetrafluorobenzene is stirred at a stirring speed of 500 to 700 rpm for 10 to 15 hours to obtain a hole transport layer solution doped with 1,4-diiodotetrafluorobenzene; (b) Preparation of hole transport layer The hole transport layer solution was statically spin-coated on the surface passivation layer of phenethylammonium iodide at a rotation speed of 3500-4500 rpm for 20-30 seconds to prepare a 1,4-diiodotetrafluorobenzene-doped spiro-OMeTAD hole transport layer; 6) Preparation of Ag electrode At a pressure of 1×10 -4 ~1×10 -3 Pa, Ag electrode was evaporated on the 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer at a growth rate of Thus, a perovskite solar cell based on 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer was obtained.

2. A perovskite solar cell based on 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer, characterized in that: The method is prepared by the method of claim 1.

3. A perovskite solar cell based on 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer as claimed in claim 2, characterized in that: The thickness of the SnO2 electron transport layer is 20 to 30 nm, the thickness of the perovskite active layer is 0.8 to 1.2 μm, the thickness of the phenethylammonium iodide surface passivation layer is 6 to 12 nm, the thickness of the 1,4-diiodotetrafluorobenzene doped spiro-OMeTAD hole transport layer is 200 to 300 nm, and the thickness of the Ag electrode is 80 to 100 nm.

Citation Information

Patent Citations

  • A method for controllable preparation of organic semiconductor nanowire by synergistic action

    CN109037448A

  • Preparation method of cation-doped perovskite solar cell

    CN110518125A